2020
DOI: 10.3390/pathogens9020114
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Pathotyping, and Antibiotic Susceptibility of Avian Pathogenic Escherichia coli among Diseased Broiler Chicks

Abstract: A total of 54 broiler flocks during the first two weeks of life was used to investigate the incidence of avian pathogenic E. coli in Egypt; 28 isolates (51.85%) were revealed by colony morphology and biochemical identification which then investigated for their serogroups and only 18/28 isolates were serotyped. The most prevalent serotypes were O115, O142, O158, O55, O125, O114, O27, O20, and O15. By application of polymerase chain reaction (PCR), 83.3% (15/18) of the serotyped isolates were confirmed to be E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
7
25
1
Order By: Relevance
“…We found all the APEC isolates to be resistant to ampicillin and tetracycline, and a high prevalence of resistance to chloramphenicol, erythromycin, enrofloxacin, norfloxacin, and ciprofloxacin. A 100% resistance of APEC isolates to ampicillin and tetracycline was also reported by Awad et al [ 67 ]. In addition, Subedi et al [ 17 ] and Ozawa et al [ 68 ] reported higher percentages of APEC resistance to ampicillin, tetracycline, ciprofloxacin, and norfloxacin.…”
Section: Discussionsupporting
confidence: 62%
“…We found all the APEC isolates to be resistant to ampicillin and tetracycline, and a high prevalence of resistance to chloramphenicol, erythromycin, enrofloxacin, norfloxacin, and ciprofloxacin. A 100% resistance of APEC isolates to ampicillin and tetracycline was also reported by Awad et al [ 67 ]. In addition, Subedi et al [ 17 ] and Ozawa et al [ 68 ] reported higher percentages of APEC resistance to ampicillin, tetracycline, ciprofloxacin, and norfloxacin.…”
Section: Discussionsupporting
confidence: 62%
“…Adherence in APEC is facilitated primarily by type 1 fimbriae, P fimbriae, and S fimbriae [ 2 , 31 ]. Several genes encoding these fimbriae and additional adhesins, fim H, fim C (type 1 fimbriae), pap A, pap C, pap EF, pap G I, pap G II, pap GIII, fel A (P fimbriae), sfa / sfa S (S fimbriae), foc GE (F1C fimbriae), afa IBC (afimbriae), lpf A, lpf 0141, lpf 0154 (long polar fimbriae), mat / ecp A (fimbrillin), flg E (flagellar hook), crl , csg (curli), tsh (temperature-sensitive haemagglutinin), bma E (M hemagglutinin), hra / hrl A/ hek (heat-resistant agglutinin), iha (IrgA homologue adhesin), yqi G (putative outer membrane usher protein), and kii (K capsule encoding genes) have been reported in APEC [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These adhesins also mediate motility, biofilm formation, and APEC survival in macrophages [ 31 ].…”
Section: Virulence and Pathogenesis Factorsmentioning
confidence: 99%
“…Many antibiotics belonging to different classes, such as tetracyclines (tetracycline, oxytetracycline, chlortetracycline), sulfonamides (sulfadimethoxine, trimethoprim, sulfadiazine, sulfamethazine, sulfaquinoxaline, ormethoprim), aminoglycosides (apramycin, gentamicin, neomycin, spectinomycin), penicillins (amoxicillin, ampicillin), cephalosporins (ceftiofur), quinolones (danofloxacin, sarafloxacin, enrofloxacin), polymyxins (colistin), chloramphenicols (florfenicol), macrolides (erythromycin), and lincosamides (lincomycin) have been used in poultry industry worldwide for the control of APEC infections [ 23 ]. However, APEC resistance to multiple antibiotics has been reported [ 32 , 34 , 35 , 51 , 53 , 54 , 70 , 71 , 72 , 73 , 107 , 108 , 108 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ], which limits the use of these antibiotics and suggests a challenge ahead in using these antibiotics. Table 2 provides a summary of antibiotic resistance and resistance genes (mechanisms) reported worldwid...…”
Section: Control Strategiesmentioning
confidence: 99%
“…Within the poultry gastrointestinal tract, bacteria exist at high densities thus facilitating intra-and inter-species, as well as inter-genera, horizontal transfer of resistance genes (Cordoni et al, 2016;Card et al, 2017). APEC are often resistant to a range of antimicrobial compounds including tetracyclines, chloramphenicol, sulphonamides fluoroquinolones and β-lactams (Solà-Ginés et al, 2015;Awad et al, 2016;Hornsey et al, 2019;Awad et al, 2020). The genes conferring resistance are frequently encoded on integrons and plasmids, as well as other mobile genetic elements, which can be passed between permissive APEC strains and other species (Hornsey et al, 2019;Cummins et al, 2019).…”
Section: Wgs Can Improve Surveillance Of Amr and Aid The Characterization Of Gene Transmission Dynamicsmentioning
confidence: 99%
“…APEC classification is traditionally based on serotyping and virulence genotyping, with the gold standard for designation of a pathogenic E. coli isolate as APEC being confirmation of virulence in day-old chicks or embryos (Dho & Lafont, 1982;Awad et al, 2020.). However, this is now rarely performed due to a lack of suitable facilities, and ethical concerns.…”
Section: Introductionmentioning
confidence: 99%